In search of the soul a philosophical essay - Cottingham, John, 1943- (Princeton University Press, 2020)
The concept of the soul has been a recurring area of exploration since ancient times. What do we mean when we talk about finding our soul, how do we know we have one, and does it hold any relevance in today's scientifically and technologically dominated society? From Socrates and Augustine to Darwin and Freud, In Search of the Soul takes readers on a concise, accessible journey into the origins of the soul in Western philosophy and culture, and examines how the idea has developed throughout history to the present. Touching on literature, music, art, and theology, John Cottingham illustrates how, far from being redundant in contemporary times, the soul attunes us to the importance of meaning and value, and experience and growth. A better understanding of the soul might help all of us better understand what it is to be human. Cottingham delves into the evolution of our thoughts about the soul through landmark works-including those of Aristotle, Plato, and Descartes. He considers the nature of consciousness and subjective experience, and discusses the psychoanalytic view that large parts of the human psyche are hidden from direct conscious awareness. He also reflects on the mysterious and universal longing for transcendence that is an indelible part of our human makeup. Looking at the soul's many dimensions-historical, moral, psychological, and spiritual-Cottingham makes a case for how it exerts a powerful pull on all of us. In Search of the Soul is a testimony to how the soul remains a profoundly significant aspect of human flourishing.